Case Report: Atropine-induced delirium in a dog - Fedotova, Samantha; Kellihan, Heidi B.; Smith, Lesley; Bartholomew, Kyle (Frontiers in Veterinary Science, 2025)
A 6-year-old spayed female Goldendoodle was presented as a referral for bradycardia and collapse. An electrocardiogram revealed a high-grade second-degree atrioventricular block (HG2AVB) with atrial flutter. The patient was hospitalized overnight with the intention of pacemaker placement the following morning. Following bolus administration of atropine and lidocaine to rule out high vagal tone, the patient was placed on an atropine continuous rate infusion (CRI) to increase heart rate overnight. This resulted in an acute onset of suspected delirium, which lasted several hours following cessation of the CRI. The patient proceeded with pacemaker placement the following day. No further neurological events were noted at 1 year after pacemaker placement. Atropine-associated delirium should be considered in any patient where high cumulative doses of atropine are being considered.